Who was Helen Keller? /Biography-Easy reader - Thompson, Gare.; Harrison, Nancy, 1963- (New York : Grosset & Dunlap, 2003)
A biography of the woman who, with the assistance of her devoted teacher Annie Sullivan, achieved success and fame despite being blind and deaf.
Keywords: Keller, Helen, -- 1880-1968 -- Juvenile literature; Keller, Helen, -- 1880-1968.; Sullivan, Annie, -- 1866-1936.; Deafblind women -- United States -- Biography -- Juvenile literature; Deafblind women -- United States -- Education -- Juvenile literature; Blind; Deaf; People with disabilities; Women -- Biography